Diverting the crystallization route: magadiite-to-mordenite hydrothermal conversion - Chaves , Rafael; Martinez-Ortigosa, Joaquin; Fernandes Barbosa, Felipe; Pinheiro Braga, Tiago; Wittee Lopes, Christian; Castellã `Pergher, Sibele Berenice (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Layered solids have attracted significant attention due to their variety, being promising for modifications to produce different materials. Magadiite is a hydrous layered silicate already used as a silica source for obtaining zeolites. However, its structure was recently solved, providing consistent information to the understanding of these modifications. Thus, this work studied an interconversion method to transform pure magadiite into zeolite mordenite. The synthesis method applied is distinct as it occurs in a single system through a stepped hydrothermal treatment, providing a new perspective on the phase transition.